The Effect of the STAD Cooperative Learning Model on Students' Cooperation Attitude in the Subject of Pancasila Education - Adinda Ayu Effendi; Misriandi (Global Synthesis in Education Journal, 2024)
Cooperative learning strategies have been widely recognized for enhancing interpersonal skills and fostering positive student attitudes. The Student Teams Achievement Divisions (STAD) model emphasizes structured group work and individual accountability, which are crucial in cultivating cooperative attitudes. In the context of Pancasila Education—a foundational course aimed at instilling national ideology and character building in Indonesian students—the integration of effective cooperative learning models is essential for promoting social harmony and civic responsibility. This study aims to investigate the effect of the STAD Cooperative Learning Model on students' cooperation attitudes within the framework of Pancasila Education. Specifically, it seeks to determine whether the implementation of the STAD model significantly enhances cooperative behaviors and attitudes among high school students engaged in the Pancasila curriculum. A quasi-experimental research design was employed, involving two groups of high school students enrolled in Pancasila Education classes. The experimental group participated in the STAD cooperative learning model, while the control group followed traditional instructional methods. Data were collected using a validated cooperation attitude questionnaire administered before and after the intervention. The sample comprised 200 students selected through stratified random sampling to ensure representativeness. Statistical analyses, including paired t-tests and ANCOVA, were conducted to evaluate the effectiveness of the STAD model. Preliminary findings indicate that students exposed to the STAD cooperative learning model exhibited a significant improvement in their cooperation attitudes compared to the control group (p < 0.05). The experimental group showed enhanced abilities in teamwork, communication, and mutual support, aligning with the core principles of Pancasila Education. Additionally, subgroup analyses revealed that the positive effects of the STAD model were consistent across different demographic variables, including gender and socio-economic status.